Where, when, and why young athletes use imagery: An examination of developmental differences - Munroe-Chandler, K. J.; Hall, C. R.; Fishburne, G. J.; Strachan, L. (Research Quarterly for Exercise and Sport, 2007)
The purpose of this study was to investigate young athletes` imagery use from a developmental perspective. The participants were 110 male and female athletes competing in both team and individual sports. They represented four different age cohorts (i.e., 7-8, 9-10, 11-12, and 13-14 years). Sixteen focus groups, two for each age category and gender, were used as the method of data collection. The findings indicated "where," "when," and "why" young athletes use imagery and how imagery use changes as children move from early childhood through to early adolescence. Overall, results revealed that all age cohorts reported using imagery in both training and competition and for both cognitive and motivational purposes. The present research also found support for studying imagery use by young athletes from a developmental perspective.